TAP! TAP! TAP ! COHERENCES OF ONOMATOPOEIC EXPRESSION BETWEEN THE SONG TITLES AND THE THEMES IN KOREAN POP SONGS - Keyla Safirna Rechan; Khodijah Gadis Arivia; Romadon Budi Utomo; Eva Zulianti (Ma Chung Press, 2026)
: K-pop has become part of Korean culture attracting international attention. Behind its dazzling success, K-pop has various interesting elements. One of the main attractions in this industry is the songs. Creative ideas abound in the writing of lyrics and the selection of song titles. One such element is the use of onomatopoeia, as seen in the numerous songs with unique or even strange-sounding lyrics, such as bang bang bang, clik clak, and boom. This study aims to analyze the consistency of onomatopoeia usage in K-pop song titles. We use a theory based on Vilma Kokko's (2013) theory of six types of sound effects based on their source to analyze the types of onomatopoeia in K-pop song titles. How these types of onomatopoeia cohered with the songs is analyzed using Walter Fisher's (2010) theory, which states that coherence is based on three specific types of coherences. Techniques of analysis by Spradley (1980) were employed in this study. The main findings of this study indicate that onomatopoeia in K-pop song titles are not merely decorative or distinguishing elements, but play an important role both semantically and symbolically. The types of onomatopoeia most frequently used as song titles are impact, air current, explosions, and gunshots. This study aims to contribute to the understanding of semiotic strategies in contemporary Korean pop music. Further research could combine lyrics, images, and music video backgrounds in an objective manner in order to fully understand the metaphors, symbolism, messages conveyed by artists, and cultural values.